Performance tests of dual-phase CO2 cooling for particle detectors. Issue 1 (1st November 2022) - Arling, J-H; Baselga, M; Diez, S; Gregor, I-M; Goettlicher, P; Gupta, R; Hauser, M; Parzefall, U; Poblotzki, F; Renardi, A; Schmitt, S; Sperlich, D; et al.
Abstract : Evaporative CO2 cooling is becoming a popular cooling solution for large-scale, high-energy particle detectors, such as the new ATLAS Inner Tracker (ITk) for the high-luminosity upgrade of the LHC. CO2 offers a high latent heat transfer at reasonable flow parameters and is an environment friendly alternative to many other coolants currently used. This cooling technique is used to investigate the thermal performance of prototypes from the ITk strip detector produced at DESY. The strip end-cap local support structure, called petal core, is designed to allow a good heat transfer between silicon strip modules glued on its surface and the embedded titanium cooling pipe. Studies on the thermal properties using infrared thermography have been performed to analyse the heat dissipation path which allows also to detect eventual imperfections in the assembly as part of the quality control strategy. A similar analysis was executed on a petal loaded with electrical modules to study the heat generation due to active components and its dissipation for each module under different CO2 conditions.